Analyse der akademischen Orientierungen von Studierenden: Ein binationaler Vergleich - Māra Vidnere (International Dialogues on Education: Past and Present, 2017)
The current conditions of economic variations impact the quality of student teachers’ training, their professional competence, and especially that of education, to a great degree. There is a noticeable trend in the labour market of a demand for occupations with high professional qualities, i.e., respective education. Consequently the social importance of pedagogy as a scientific discipline is increasing, and research about students’ academic interests are particuarly important today. A requirement for the effectiveness of this research is ist the ualiy of the research activity, that is if it meets the needs of personalities and of society. A sound foundation for the quality of the research is the development of the scientific methodology. For the development of pedagogy both sides are important—methodology and social function. To achieve successful with a professional activity the pedagogue must decide on his or her developmental aims and discover optimal possible ways to achieve them, be convinced of his/her choice of interests, and secure in and aware of his/her own values. The methodology develops in unity with the development of the pedagogy. In the following contribution the attitudes of student teachers towards their studies is analyzed as their academic orientation during the process of professional identity formation. The object of the methodology of the scientific discipline of pedagogy is resarch activity. The aim of this present study focuses on the orientations and interests of the students with regard to the teaching profession. Students’ orientations were analyzed as their academic orientation in the process of the development of their professional identity. The research adapted the survey about academic orientation (Davidson, Beck & Silver, 1999). The adaptation of the methodologies was conducted under the guidance of professors M. Vidnere and A. Špona and comprised 36 questions on the analysis of academic orientations by students. The question arises if student teachers develop a special area of interest which points to a specific academic orientation.